Parameters for Simulation of Adult Subjects During Mechanical Ventilation - Arnal, Jean-Michel; Garnero, Aude; Saoli, Mathieu; Chatburn, Robert L (Respiratory care, 2018)
Simulation studies are often used to examine ventilator performance. However, there are no standards for selecting simulation parameters. This study collected data in passively-ventilated adult human subjects and summarized the results as a set of parameters that can be used for simulation studies of intubated, passive, adult subjects with normal lungs, COPD, or ARDS. Consecutive adult patients admitted to the ICU were included if they were deeply sedated and mechanically ventilated for <48 h without any spontaneous breathing activity. Subjects were classified as having normal lungs, COPD, or ARDS. Respiratory mechanics variables were collected once per subject. Static compliance was calculated as the ratio between tidal volume and driving pressure. Inspiratory resistance was measured by the least-squares fitting method. The expiratory time constant was estimated by the tidal volume/flow ratio. Of the 359 subjects included, 138 were classified as having normal lungs, 181 as ARDS, and 40 as COPD. Median (interquartile range) static compliance was significantly lower in ARDS subjects as compared with normal lung and COPD subjects (39 [32-50] mL/cm H O vs 54 [44-64] and 59 [43-75] mL/cm H O, respectively, < .001). Inspiratory resistance was significantly higher in COPD subjects as compared with normal lung and ARDS subjects (22 [16-33] cm H O/L/s vs 13 [10-15] and 12 [9-14] cm H O/L/s, respectively, < .001). The expiratory time constant was significantly different for each lung condition (0.60 [0.51-0.71], 1.07 [0.68-2.14], and 0.46 [0.40-0.55] s for normal lung, COPD, and ARDS subjects, respectively, < .001). In the subgroup of subjects with ARDS, there were no significant differences in respiratory mechanics variables among mild, moderate, and severe ARDS. This study provides educators, researchers, and manufacturers with a standard set of practical parameters for simulating the respiratory system's mechanical properties in passive conditions.